Dual role of autoantibodies to heat shock proteins in autoimmune diseases - Tukaj, Stefan (Frontiers in Immunology, 2024)
Autoimmune diseases are characterized by the recognition of self-antigens (autoantigens) by immune system cells. Loss of immunological tolerance may lead to the generation of autoantibodies and, consequently, tissue damage. It has already been proven that highly immunogenic bacterial and autologous extracellular heat shock proteins (eHsps) interact with immune cells of the innate and adaptive arms of the immune system. The latter interactions may stimulate a humoral (auto)immune response and lead to the generation of anti-Hsps (auto)antibodies. Although circulating levels of anti-Hsps autoantibodies are often elevated in patients suffering from multiple inflammatory and autoimmune diseases, their role in the development of pathological conditions is not fully established. This mini-review presents the dual role of anti-Hsps autoantibodies -protective or pathogenic -in the context of the development of selected autoimmune diseases.